An Isolated Zinc–Cobalt Atomic Pair for Highly Active and Durable Oxygen Reduction. (5th February 2019) - Lu, Ziyang; Wang, Bo; Hu, Yongfeng; Liu, Wei; Zhao, Yufeng; Yang, Ruoou; Li, Zhiping; Luo, Jun; Chi, Bin; Jiang, Zheng; Li, Minsi; Mu, Shichun; et al.
Abstract: A competitive complexation strategy has been developed to construct a novel electrocatalyst with Zn‐Co atomic pairs coordinated on N doped carbon support (Zn/CoN‐C). Such architecture offers enhanced binding ability of O2, significantly elongates the O−O length (from 1.23 Å to 1.42 Å), and thus facilitates the cleavage of O−O bond, showing a theoretical overpotential of 0.335 V during ORR process. As a result, the Zn/CoN‐C catalyst exhibits outstanding ORR performance in both alkaline and acid conditions with a half‐wave potential of 0.861 and 0.796 V respectively. The in situ XANES analysis suggests Co as the active center during the ORR. The assembled zinc–air battery with Zn/CoN‐C as cathode catalyst presents a maximum power density of 230 mW cm −2 along with excellent operation durability. The excellent catalytic activity in acid is also verified by H2 /O2 fuel cell tests (peak power density of 705 mW cm −2 ). Abstract : Diskrete Behandlung : Diskrete Zn/Co‐Dimetallzentren wurden durch kompetitive Komplexierung auf N‐dotiertem Kohlenstoff aufgebracht (Zn/CoN‐C). Zn/CoN‐C katalysiert hocheffizient die Sauerstoffreduktion unter alkalischen wie auch sauren Bedingungen. Eine Zn‐Luft‐Batterie und eine H2 /O2 ‐Brennstoffzelle mit diesem Katalysator zeigen eine exzellente Leistungsdichte und Stabilität, was ihre Praxistauglichkeit demonstriert.